1992
DOI: 10.1590/s0006-87051992000200004
|View full text |Cite
|
Sign up to set email alerts
|

Fotossíntese, remobilização de reservas e crescimento de grãos em dois híbridos de milho sob deficiência hídrica na fase de enchimento dos grãos

Abstract: Foram avaliados, em dois híbridos simples de milho (Zea mays L.), Pioneer 3072 e IAC 701 x B, submetidos à deficiência hídrica, o comportamento da fotossíntese, da remobilização de N e de açúcares durante o período de crescimento dos grãos. As plantas foram cultivadas sob condições naturais, em doze tanques de alvenaria (4 m de comprimento x 0,5 m de largura x 0,6 m de profundidade) contendo terra. A deficiência hídrica foi induzida entre o 5.º e o 15.º dia após a floração, suspendendo-se a irrigação. Sem defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
1
2
0
6
Order By: Relevance
“…According to FRENCH & TURNER (1991), a moderate water deficiency can lead to a biomass reallocation to produce grain, which, in the case of Lupinus angustifolius, was expressed as an increase in the number of seeds per pod. The same pattern of reallocation has been observed in corn, mainly in strains more tolerant to water deficit (MACHADO et al, 1992). Total leaf area (LA) was higher in the conventional cultivar in both water conditions than transgenic one, but it was reduced (P<0.05) in both cultivars under water deficiency.…”
Section: Water Replenishment ---------------------100%---------------supporting
confidence: 60%
“…According to FRENCH & TURNER (1991), a moderate water deficiency can lead to a biomass reallocation to produce grain, which, in the case of Lupinus angustifolius, was expressed as an increase in the number of seeds per pod. The same pattern of reallocation has been observed in corn, mainly in strains more tolerant to water deficit (MACHADO et al, 1992). Total leaf area (LA) was higher in the conventional cultivar in both water conditions than transgenic one, but it was reduced (P<0.05) in both cultivars under water deficiency.…”
Section: Water Replenishment ---------------------100%---------------supporting
confidence: 60%
“…Considering that there was less available water in 2011 and the cycle was reduced in approximately 30 days, it is suggested that the plant had allocated the reserves to the seeds, firstly from the primary stems. Machado et al (1992) evaluated the remobilization of reserves in two hybrids of maize under water deficiency after flowering and found a reduction in stem dry matter only in the treatments with water deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Após às 9h com o aumento da demanda evaporativa (DPV arfolha ) e em função do aumento da temperatura (Figura 4) os incrementos em DFFFA não causaram aumento em A, ocorrendo também saturação lumínica. MACHADO et al (1992) também observaram saturação lumínica e queda em A nos horários mais quentes do dia em dois híbridos de milho submetidos ao estresse hídrico. Em geral, nas plantas C4 como o milho, não há saturação lumínica na fotossíntese.…”
Section: Introductionunclassified
“…A abertura estomática foi crescente com o aumento de DFFFA, porém de forma característica para cada estádio fisiológico relativo à medida. No estádio vegetativo (V 8 ) gs aumentou até 0,6 mol m -2 s -1 com DFFFA até valores próximos a 1500 μmol m -2 s -1 , quando então a saturação luminosa foi atingida, concordando com os valores citados por MACHADO et al (1992) também em milho. Na segunda e terceira séries de medidas, nos estádios V T e R 4 , gs já atingiu seu valor máximo ao redor das 8h30, 0,45 e 0,2 mol m -2 s -1 , respectivamente, quando DFFFA foi ao redor de 1200 μmol m -2 s -1 .…”
Section: Introductionunclassified
See 1 more Smart Citation